2015
DOI: 10.1155/2015/170278
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondiiInfection in Pregnant Women: A Seroprevalence and Case-Control Study in Eastern China

Abstract: Very limited information is available concerning the epidemiology of T. gondii infection in pregnant women in eastern China. Therefore, a case-control study was conducted to estimate the seroprevalence of toxoplasmosis in this population group and to identify risk factors and possible routes of contamination. Serum samples were collected from 965 pregnant women and 965 age-matched nonpregnant control subjects in Qingdao and Weihai between October 2011 and July 2013. These were screened with enzyme linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 27 publications
4
31
7
Order By: Relevance
“…gondii in study population [35]. Consumption of raw/undercooked meat is one of the studied risk factors in our study that was not statistically significant (P=0.4 and P=0.5 in thalassemia patients and control individuals, respectively).…”
Section: Hepatitis C Virus (Hcv) Human Immunodeficiency Virus (Hiv)contrasting
confidence: 66%
See 1 more Smart Citation
“…gondii in study population [35]. Consumption of raw/undercooked meat is one of the studied risk factors in our study that was not statistically significant (P=0.4 and P=0.5 in thalassemia patients and control individuals, respectively).…”
Section: Hepatitis C Virus (Hcv) Human Immunodeficiency Virus (Hiv)contrasting
confidence: 66%
“…Consumption of raw/undercooked meat is one of the studied risk factors in our study that was not statistically significant (P=0.4 and P=0.5 in thalassemia patients and control individuals, respectively). In some studies it has been shown that consumption of raw meat is not correlated with toxoplasmosis [5,[35][36][37][38] while results of other investigations are in contrast [9,10]. Risk factors like gender, residence, age group, educational level, ethnicity and source of drinking water which have been detailed in Table 2, were not statistically significant in current study.…”
Section: Hepatitis C Virus (Hcv) Human Immunodeficiency Virus (Hiv)contrasting
confidence: 60%
“…In our study, the Toxoplasma gondii seropositivity was relatively low among Chinese women of reproductive age: 2.3% were IgG positive and 0.3% were IgM positive, whereas 0.04% were both IgG and IgM positive. Toxoplasma gondii IgG and IgM seropositivity among pregnant women in China has been previously reported to be 3.8% and 1.6%, respectively, in Jiangsu province and 15.2% and 2.9%, respectively, in Qingdao and Weihai cities . An IgG seropositivity rate of 21.6% has been reported in Dali among all age groups .…”
Section: Discussionmentioning
confidence: 95%
“…For toxoplasmosis caused by the infection of Toxoplasma gondii, approximately 14% of the individuals in the United States are seropositive to it by the age of 40 years (Saheb, 2018). At the same time, the prevalence of Toxoplasma gondii infection also has been found in some American countries (Cong et al, 2015).…”
Section: Hazards and Risks Of Protozoamentioning
confidence: 99%